Neutropenic Enterocolitis Disclosing an Underlying Cyclic Neutropenia - Fatima Ezzahra Lahlimi; Khawla Khalil; Soumia Lahiaouni; Illias Tazi (Case Reports in Pediatrics)
Neutropenic enterocolitis is a syndrome characterized by fever and abdominal pain in a neutropenic patient. It is often reported in children treated for leukemia and rarely reported in patients with other diseases. Herein, we report the case of a 9-year-old patient with a medical history of recurrent fever and mouth ulcers since the age of 4, who presented with neutropenic enterocolitis complicated with intestinal perforation which all leaded to disclose cyclic neutropenia. The patient was successfully treated by aggressive supportive care combined with surgical intervention. Neutropenic enterocolitis with possible complications should be considered and promptly managed in every neutropenic patient and may reveal a rare cause of neutropenia as cyclic neutropenia.